PENGELOLAAN OBJEK WISATA PANTAI INDAH SERGANG DI DESA TANJUNG HARAPAN KECAMATAN SINGKEP KABUPATEN LINGGA TAHUN 2016 - ", Hanjani; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Indah Sergang Beach tourist attraction is one of the attractions in Lingga Regency, which is located in the village of Tanjung Harapan, Singkep District, Lingga Regency. Indah Sergang Beach is a tourist attraction that originally came from the self-supporting community of Tanjung Harapan Village and began to be built in 2008 by the Lingga district tourism office. The attractions of Indah Sergang Beach include beaches with sloping white sand, clean sea water, and a beach position that faces directly to the sunrise. Indah Sergang Beach has the potential to be developed, proper management will add value to sales and become a source of income for the community and local government. The formulation of the problem from this research is How is the management of Indah Sergang Beach tourism object in Tanjung Harapan Village, Singkep District, Lingga Regency, 2016?            This study aims to determine the management of Indah Sergang Beach attractions in Tanjung Harapan Village, Singkep District, Lingga Regency, 2016 and constraints in the management of  Indah Sergang Beach tourism object. This study uses a qualitative research approach with a type of descriptive research. Data collection techniques used were interviews and documentation. Data analysis is carried out interactively and continuously until complete, so the data is saturated.             The results showed that the tourist attraction of Indah Sergang Beach was managed by the Department of Tourism, Youth and Sports, Lingga Regency and the community was assigned directly as cleaning staff at Indah Sergang Beach. The management of Indah  Sergang Beach tourism object has not been managed optimally, this can be seen from the process of planning, organizing, actuating and controlling. Constraints that make this region not yet managed optimally include the lack of a budget which has an impact on the maintenance of facilities and infrastructure at tourist sites, there is no institution that manages tourism objects, there are no regulations governing the implementation of activities in tourist attractions in detail, retribution management is not implemented anymore in the management of Indah Sergang Beach because the method of collecting previous retributions is not in accordance with regulations and training activities for tourism conscious people in Tanjung Harapan Village community are still lackingKeywords: Planning, Organizing, Actuating, Controlling.